Yield potential of Spring Wheat Influenced by Crop Residue, Tillage System and Nitrogen Rate on irrigated land - Asad Shah,; Mohammad Akmal,; Mohammad Arif,; Mohammad Jamal Khan, (Universiti Kebangsaan Malaysia, 2014)
Yield performance in wheat (Triticum aestivum) was compared under crop residue, tillage system and nitrogen rate treatments in cereal based cropping system. The experiments were conducted at Agronomy Research Farm, The University of Agriculture, Peshawar, in 2009-2010 and 2010-2011. Chopped crop residue on dry matter basis (5 t ha-1) of legume (Vigna unguicuata, var. Ebney) and cereal (Zea mays, var. Azam) was applied in main plots with no residue treatments and plowed with Mould Board (MB) and Cultivator as deep and shallow treatments, respectively. A month after the crop residue and tillage system treatments, field was uniformly plowed with cultivator and wheat was sown with drill in rows 25 cm apart in the month of November on both years. Both P2O5 and K2O (80 and 40 kg ha-1, respectively) were applied uniformly to all fields before sowing. Nitrogen as subplot treatment (0, 40, 80, 120 and 160 kg ha-1) was applied in two splits, half at 15 and the other half at 45 days after sowing with uniform cultural practices for crop growth and development. Compared to year 1, crop of year 2 showed better phenology with extended life cycle (LC). On two years average across tillage and N treatments, biological yield did not change (p<0.05) under the residue but did report lower at no-residue treatment. Nonetheless, grain yield showed a significant (p<0.05) change with the highest in legume followed by cereal and the lowest in no-residue treatments. A non-significant tiller number and significant variations in grain weight and spike m-2 were observed that influenced the grain and biological yield differently. Deep than shallow tillage resulted in better traits, which returned better biomass and grain yield. Nitrogen application from control to every increment showed a significant (p<0.05) improvement in all observations contributing in yield. The study confirms the significance of legume vs. cereal over no-crop residue incorporated through deep tillage system with optimum N (120 kg ha-1) in cereal-based cropping system for sustainable performance to sustain soil C:N for future production.